Ludwig Wittgenstein’s philosophy in the light of the diagnosis of Autism - Silva, Gustavo Augusto Fonseca (Griot : Revista de Filosofia, 2023)
Psychiatrists such as Michael Fitzgerald, Christopher Gillberg and Yoshiki Ishisaka diagnosed Ludwig Wittgenstein posthumously with Autism Spectrum Disorder (ASD). Taking this diagnosis into account, the present paper discusses how Wittgenstein’s philosophy reveals his cognitive difficulties. Wittgenstein’s grammatical inquiries are particularly investigated here, highlighting his misunderstandings concerning the use of words – specially, his misunderstandings concerning analogies, which he tended to interpret literally.